Chemical Warfare Agents: Structure, Properties, Decontamination (Part 2) - Olexander E. Shumeiko; Mykola I. Korotkikh (Журнал органічної та фармацевтичної хімії)
The review is aimed at summarizing and systematizing information about various methods of deactivation of chemical warfare agents that are necessary on the battlefield, as well as in laboratories, research institutions, and facilities of production, storage, and destruction of poisonous substances. The review presents the main directions of neutralizing warfare poisonous substances, which are the most effective in the conditions of their real use. In the second part of this work, the methods of deactivating warfare poisons using nucleophilic reagents, primarily α-nucleophiles, which have high efficiency and can react as nucleophiles and as oxidants, are considered in detail. A promising area of degradation of such products is the use of supernucleophilic systems based on functionalized detergents, as well as adsorption and photocatalytic deactivation methods. The material presented above shows the importance of general knowledge about the physical and chemical properties of chemical warfare agents, the rate of their decomposition, the advantages and disadvantages of certain available technologies for their application. This review can be useful for finding new and improving known methods for decontamination of chemical warfare agents and other ecotoxicants, and protecting the environment.